A cost-effective process chain for thermoplastic microneedle manufacture combining laser micro-machining and micro-injection moulding. (January 2021) - Gülçür, Mert; Romano, Jean-Michel; Penchev, Pavel; Gough, Tim; Brown, Elaine; Dimov, Stefan; Whiteside, Ben
Highlights: A microneedle mould insert has been produced using laser micro-machining in less than 45 min. State-of-the-art micro-injection moulding has been used for replication of the microneedle cavities. An automated, bespoke measurement apparatus for the quality assessment of microneedles has been developed. Process data have been interrogated for in-line quality assurance of microneedle arrays. Abstract: High-throughput manufacturing of transdermal microneedle arrays poses a significant challenge due to the high precision and number of features that need to be produced and the requirement of multi-step processing methods for achieving challenging micro-features. To address this challenge, we report a flexible and cost-effective process chain for transdermal microneedle array manufacture that includes mould production using laser machining and replication of thermoplastic microneedles via micro-injection moulding (micromoulding). The process chain also incorporates an in-line manufacturing data monitoring capability where the variability in the quality of microneedle arrays can be determined in a production run using captured data. Optical imaging and machine vision technologies are also implemented to create a quality inspection system that allows rapid evaluation of key quality indicators. The work presents the capability of laser machining as a cost-effective method for making microneedle moulds and micro-injection moulding of thermoplastic microneedle arrays as a highly-suitable manufacturing technique for large-scale production with low marginal cost.